The effectiveness of COVID-19 surveillance applications in Uganda: assessment of a medical rapid response system - Goswami, Nandu; Acanit, Mary; Buwule, Robert Stalone; Schmid-Zalaudek, Karin; Brix, Bianca (My University, 2024)
Different Information Communication Technologies (ICTs) health-based innovations such as cloud computing, web and mobile surveillance applications were used by proactive governments to fight COVID-19. Contact tracing mobile applications were used by more than 100 countries. However, the extent to which these surveillance applications have been used to track Covid-19 in Uganda is not clear. This study aimed to establish the use of COVID-19 surveillance applications in Uganda. This was a purely qualitative study. Health practitioners managing these surveillance applications were interviewed from Kampala City, Mukono and Wakiso districts of Uganda. The assessment of the COVID-19 surveillance applications underscores the relevance of health-based ICTS. The surveillance applications provided accurate, authoritative and timely data. However, there were false alerts as result of inaccurate data supplied by the applications. The study recommends increased facilitation of the surveillance officers, continuous training of surveillance teams and integration of the applications for the management of other non-communicable diseases.
Keywords: Surveillance applications; Health based ICTs; COVID-19; Uganda